2014
DOI: 10.1002/eji.201343986
|View full text |Cite
|
Sign up to set email alerts
|

Vasostatin‐1 antigenic epitope mapping for induction of cellular and humoral immune responses to chromogranin A autoantigen in NOD mice

Abstract: Additional supporting information may be found in the online version of this article at the publisher's web-site IntroductionChromogranin A (ChgA) is a prohormone in neuroendocrine tissues that is a target of pathogenic CD4 + T cells in NOD mice [1,2].This prohormone is an acidic secretory protein found in the granules of neuroendocrine cells, and can be cleaved to form functional proteins, including vasostatin-1 (VS-1, ChgA 1-76), vasostatin-2 (VS-2, ChgA 1-113), and WE-14 [3]. In pancreatic β-cells, VS-1 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
8
1
Order By: Relevance
“…Our functional and structural data presented here led us to conclude that WE14 is an essential part of the epitope for a diverse set of ChgA-specific CD4 + T cells in vivo. Another laboratory has reported that a different unrelated ChgA peptide is the natural epitope for transgenic BDC-2.5 T cells (16,17), but we were not able to reproduce this finding here with the BDC-2.5 hybridoma, perhaps due to sensitivity differences between hybridomas and the transgenic T cells. However, we show here that a set of T-cell hybridomas, including BDC-2.5, whose TCRs contain a variety of Vα, Jα, Vβ, and Jβ segments and CDR3 loops, all respond to the RLGL-WE14 peptide at low concentrations, to the WE14 peptide at high concentrations, and to pancreatic islets from WT ChgA mice, but not ChgA knockout mice.…”
Section: Cd4contrasting
confidence: 62%
See 1 more Smart Citation
“…Our functional and structural data presented here led us to conclude that WE14 is an essential part of the epitope for a diverse set of ChgA-specific CD4 + T cells in vivo. Another laboratory has reported that a different unrelated ChgA peptide is the natural epitope for transgenic BDC-2.5 T cells (16,17), but we were not able to reproduce this finding here with the BDC-2.5 hybridoma, perhaps due to sensitivity differences between hybridomas and the transgenic T cells. However, we show here that a set of T-cell hybridomas, including BDC-2.5, whose TCRs contain a variety of Vα, Jα, Vβ, and Jβ segments and CDR3 loops, all respond to the RLGL-WE14 peptide at low concentrations, to the WE14 peptide at high concentrations, and to pancreatic islets from WT ChgA mice, but not ChgA knockout mice.…”
Section: Cd4contrasting
confidence: 62%
“…3A). They also all responded to high concentrations of the weakly stimulatory natural WE14 peptide, but not to another ChgA peptide (amino acids 11-24, DTKVMKCVLEVISD) that has been suggested by others (16,17) to be the natural ChgA epitope for BDC-2.5 (Fig. 3B).…”
Section: Resultsmentioning
confidence: 65%
“…Six-to 8-week-old NOD mice were immunized subcutaneously in the hind footpad under anaesthesia with or without peptide (50 lg) emulsified in 50 ll of incomplete Freund's adjuvant (IFA) [2,3]. The draining lymph nodes were harvested after 10 days and a single-cell suspension was prepared.…”
Section: Proliferation Assays and Intracellular Cytokine Stainingmentioning
confidence: 99%
“…Vasostatin-1 and insulin are both present within the secretory granules of pancreatic islet b cells. We have reported previously that a peptide sequence of ChgA in vasostatin-1 fragment, namely ChgA 29-42, is an antigenic epitope recognized by pathogenic BDC2Á5 CD4 1 T cells in NOD mice [2,3]. Recently a hybrid molecule of insulin and ChgA sequences was reported to stimulate BDC2Á5 T cells [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation